RESTORASI EKOSISTEM MANGROVE BERBASIS PARTISIPASI MASYARAKAT BINAAN PT HENG JAYA MINERALINDO DI DESA ONE ETE, MOROWALI, SULAWESI TENGAH - afu, La Ode alirman; Sadarun, Baru; Nurgaya, Wa; salwiyah, Salwiyah; Balubi, Abdul Muis; Sabilu, Kadir; Cahyono, Harry; Nugroho, Oktsyavitto Adithya; Virginia, Chrisma; Permana, Nur; Afizha, Ainun; Emil, Wildan (Bina Bahari, 2025)
This community service program aimed to enhance the capacity of residents in One Ete Village, Morowali Regency, to restore degraded mangrove ecosystems impacted by coastal abrasion, aquaculture activities, and land exploitation. The program was designed using a participatory and collaborative approach through technical training on mangrove seedling production and planting, with Rhizophora mucronata selected as the primary species. A total of 30 participants engaged in hands-on field training covering seed propagation, nursery maintenance, and post-planting monitoring and evaluation. Seedlings were cultivated independently using a sand-soil medium in polybags and later transplanted to abrasion-prone coastal zones using spaced planting supported by bamboo stakes. Monitoring over two months recorded an 85% seedling survival rate, with early signs of ecosystem recovery such as increased fine sediment deposition and the reappearance of coastal fauna. The community also formed working groups to ensure the continued management of mangroves independently. The outcomes demonstrate that a community-based approach, integrated with technical and institutional support, can produce both ecological and social benefits and offers a replicable model for other coastal regions.